2012
DOI: 10.1520/gtj103342
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Shear Strength of an Expansive Soil by Combining a Filter Paper Method and Direct Shear Tests

Abstract: The measurement of the shear strength of unsaturated soils in terms of two independent stress state variables is usually difficult, expensive, and time-consuming. This paper presents a proposal to combine a filter paper method and a conventional direct shear test to obtain this measurement. The feasibility of this approach is illustrated through tests on an expansive soil. First, the filter paper method is used to establish the soil-water characteristic curve of the soil, and a series of conventional direct sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…In addition the apparent friction angle slightly reduced from 35.5°under unsaturated condition to 35.1°f or saturated condition. This tendency agrees very well with the results obtained by Bai and Atsumi [12,13]. Finally it can be concluded that the shear strength strongly depend on soil water content, within translate into suction force which contributed to the total shear strength of the soil.…”
Section: Static Shearing Behavioursupporting
confidence: 91%
“…In addition the apparent friction angle slightly reduced from 35.5°under unsaturated condition to 35.1°f or saturated condition. This tendency agrees very well with the results obtained by Bai and Atsumi [12,13]. Finally it can be concluded that the shear strength strongly depend on soil water content, within translate into suction force which contributed to the total shear strength of the soil.…”
Section: Static Shearing Behavioursupporting
confidence: 91%
“…Taking the matric suction as 200 kPa as the demarcation point, the shear strength in the main transition zone increases rapidly with the matric suction comparing with the secondary transition zone. This is similar to the results of Çokça and Tilgen [44], Bai and Liu [45], Pandya et al [13], and Khalili et al [22].…”
Section: Relationship Between Shear Strength and Matricsupporting
confidence: 91%
“…c hi has typically been described with soil suction [ Bishop , ; Fredlund et al ., ; Vanapalli et al ., ]. We empirically estimated c hi based on direct shear tests at different soil moisture levels and normal loads following methods developed by Matsushi and Matsukura [] (Figure a, Texts S1.2 and S2.2, and equation (S4)) and verified by others [ Bai and Liu , ; Zydron and Mietus , ; Zydron et al ., ]. Estimated matric potential using the highest observed moisture values at the most vulnerable depths for slope stability (−342 to −6 kPa) suggest positive pore pressures were unlikely at our sites (Text S1.2) [ Cosby et al ., ].…”
Section: Study Area and Methodsmentioning
confidence: 99%